Kualitas Pelanggan dan Nilai Pelanggan pada Perusahaan Freight Forwarding - Davis Prakarsa Tanod; Nofrisel Nofrisel; Sulistyawati Toelle (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2019)
This study aims to see the effect of service quality and customer value on customer loyalty at PT DHL Jakarta 2017. This research is using quantitative approach with survey method. The population of this study is the customers of PT DHL head office, Jakarta. The sample used in this study amounted to 65 respondents. The data was analyzed using validity test, reliability test, normality test, linearity, coefficient of determination, T-test, and path analysis. Based on the results of statistical tests, it can be concluded that all of the independent variables studied namely service quality and customer value have a positive influence on customer loyalty, either partially or simultaneously. Therefore customer loyalty can be increased by improving the service quality and customer value. And from the research results can be concluded that the coefficient of path variable X and to Y is 0.876 which means the direct effect of service quality with customer value, the coefficient of the path variable Y to Z is 0.942 means direct influence customer value to customer loyalty, and coefficient path variable X to Z is 0.914 means the direct influence of service quality to customer loyalty.